FP-APW + lo calculations of the elastic properties in zinc-blende III-P compounds under pressure effects - A., Bouhemadou; R., Khenata; M., Kharoubi; Yarub K.A, Al Douri; T., Seddik; Ali H., Reshak (Elsevier B.V., 2009)
Link to publisher's homepage at http://www.elsevier.com/wps/find/homepage.cws_home